The Arab Spring - Rich, Ben (2019)
In this presentation, Dr. Ben Rich will discuss the arc of the Arab Spring of 2011 and the trends that emerged in the wake of this tumultuous event. Particular focus is given to the role of state responses during the protests and uprisings across the Middle East during this periods and the tendency of these regimes to both intensify their authoritarianism and promote a wide-ranging sectarianism that continues to have ramifications to this day.